Risk Intelligence : Learning to Manage What We Don't Know - Apgar, David (2006)
In this ingenious, entertaining book, David Apgar radically revises out understanding of how to manage risk. By introducing the nation of risk intelligence, he displaces old myths with practical rules for learning about risk better and faster than anyone else can. Apgar's argument is richly illustrated with real world anecdots from business and beyond. This book should be a life guide for everyone.